2009
DOI: 10.1096/fj.09-132043
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal IGF‐1 resistance reduces Aβ accumulation and protects against premature death in a model of Alzheimer's disease

Abstract: Alzheimer's disease (AD) is characterized by progressive neurodegeneration leading to loss of cognitive abilities and ultimately to death. Postmortem investigations revealed decreased expression of cerebral insulin-like growth factor (IGF)-1 receptor (IGF-1R) and insulin receptor substrate (IRS) proteins in patients with AD. To elucidate the role of insulin/IGF-1 signaling in AD, we crossed mice expressing the Swedish mutation of amyloid precursor protein (APP(SW), Tg2576 mice) as a model for AD with mice defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
162
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 211 publications
(176 citation statements)
references
References 63 publications
13
162
1
Order By: Relevance
“…Activating the insulin/IGF pathway-which is known to inhibit FoxO factors-is important for memory retention and synaptogenesis (O'Kusky et al 2000;Aleman and Torres-Aleman 2009;Chen et al 2011). On the other hand, reducing the insulin/IGF pathwaywhich is known to activate FoxO factors-is important for extending longevity and preventing symptoms of Alzheimer's disease (Cohen et al 2009;Freude et al 2009;Killick et al 2009). It is possible that lowering the levels of insulin/IGF (leading to high FoxO activity) is beneficial for overall life span and some aspects of cognition, such as memory consolidation.…”
Section: The Paradoxical Roles Of the Insulin/igf Signaling Pathway Imentioning
confidence: 99%
See 1 more Smart Citation
“…Activating the insulin/IGF pathway-which is known to inhibit FoxO factors-is important for memory retention and synaptogenesis (O'Kusky et al 2000;Aleman and Torres-Aleman 2009;Chen et al 2011). On the other hand, reducing the insulin/IGF pathwaywhich is known to activate FoxO factors-is important for extending longevity and preventing symptoms of Alzheimer's disease (Cohen et al 2009;Freude et al 2009;Killick et al 2009). It is possible that lowering the levels of insulin/IGF (leading to high FoxO activity) is beneficial for overall life span and some aspects of cognition, such as memory consolidation.…”
Section: The Paradoxical Roles Of the Insulin/igf Signaling Pathway Imentioning
confidence: 99%
“…At the organismal level, the deletion of FoxO1 or FoxO3 results in reduced anxiety-and depression-like behaviors, respectively (Polter et al 2009). Interestingly, the insulin/ IGF pathway, which regulates FoxO transcription factors, has been found to impact learning and memory in physiological or pathological conditions such as Alzheimer's disease (Cohen et al 2009;Freude et al 2009;Killick et al 2009;Chen et al 2011). However, the importance and mode of action of the hippocampal-enriched FoxO6 in cognitive behavior are not known.…”
mentioning
confidence: 99%
“…Recent data suggest that brain-specific IGF-1 resistance increases longevity (Freude et al 2009;Kappeler et al 2008;Taguchi et al 2007). Furthermore, decreased IGF-1 signaling reduces Aβ toxicity in worms and mice (Cohen et al 2006(Cohen et al , 2009.…”
Section: Neuronal Insulin Receptor Deletion Does Not Influence Survivmentioning
confidence: 99%
“…Tg2576 mice develop an age-dependent memory impairment, Aβ accumulation and form extracellular Aβ plaques beginning at the age of 6-8 months (Stein and Johnson 2002). Furthermore, these mice display an increased mortality (Freude et al 2009). To achieve neuron-specific deletion, we crossed mice carrying a floxed exon 4 of the IR gene with mice expressing the Cre recombinase under control of the Syn-Cre.…”
Section: Neuronal Insulin Receptor Deletion Does Not Influence Survivmentioning
confidence: 99%
“…Studies using analogues for the gut hormone glucagon-like peptide-1 (GLP-1) such as liraglutide, which facilitate insulin release, have shown that even short-term treatment can improve learning and memory, in addition to improving glucose homeostasis in mice with diet-induced obesity [7]. Moreover, an increase of GLP-1 signalling in the brain has also been suggested as a promising strategy to ameliorate the degenerative processes observed in Alzheimer's disease [8], while studies crossing APP mice to mouse models with alterations in brain insulin-signalling have revealed an important role for insulin signalling and glucose homeostasis in cognitive behaviour in these mice [9][10][11].…”
Section: Introductionmentioning
confidence: 99%